FORMULASI SEDIAAN GEL EKSTRAK DAUN SUKUN (Artocarpus altilis) SEBAGAI TERAPI LUKA SAYAT PADA KELINCI NEW ZEALAND WHITE - Raharjo, Danang; Ika Dwi Ningrum; Listyani, Tiara Ajeng (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2024)
Breadfruit leaf (Artocarpus altilis) is a type of plant that has a single to oval leaf from the Moraceae family. There are secondary metabolites in breadfruit leaves (Artocarpus altilis), namely flavonoids, tannins, and saponins which are efficacious as a treatment for the wound healing process. This study aims to determine whether breadfruit leaf extract (Artocarpus altilis) can be formulated into a gel preparation and to determine the maximum concentration of breadfruit leaf extract (Artocarpus altilis) in wound healing. This study was an experimental study to determine the maximum concentration in healing cuts with varying concentrations of 6.25%, 12.5%, and 25% tested on 5 male rabbits with 3 treatment groups. Wound healing data were analyzed using One Way ANOVA (Analysis of Varian) and the physical evaluation of the gel preparation was analyzed descriptively. The results showed that breadfruit leaf extract (Artocarpus altilis) could be formulated into gel preparations and fulfilled the physical evaluation test for gel preparations. Statistical test results had a significant effect on wound healing in rabbits p=0.001 (p<0.05) and the maximum concentration in wound healing was a concentration of 25% with a healing time of 11 days.